Feedback on the use of three surgical sealants for preventing prolonged air leak after robot-assisted anatomical lung resection - Gondé, Henri; Le Gac, Constance; Gillibert, André; Bottet, Benjamin; Laurent, Marc; Sarsam, Matthieu; Hervouët, Charles; Varin, Rémi; Baste, Jean-Marc (Journal of Thoracic Disease, 2019)
Background: Prolonged air leak (PAL) is the most common complication after lung resection. Several surgical sealants have been developed to reduce PAL, including fibrin-based (FS), polyethylene glycol-based (PEGS) and polyglycolic acid-based (PGAS) sealants. In this work we report our experience of surgical sealant use after robot-assisted lung resection. Methods: A 7-year retrospective study was conducted, including patients who had robot-assisted lobectomy or segmentectomy. Data were collected using a prospective national database. The use of surgical sealants was recorded in traceability sheets. Results: PAL occurred in 60 of the 299 patients included. American Society of Anesthesiologists score (ASA) and index of prolonged air leak (IPAL) were higher for patients with sealants. In this group, operative time, chest drain duration and length of stay were significantly longer. PAL occurrence was significantly associated to sealant in univariate analysis (Odds ratio =1.88, 95% CI: 1.07 to 3.36, P=0.03) but the association was slightly decreased when adjusting on IPAL and ASA score (Odds ratio =1.70, 95% CI: 0.94 to 3.10, P=0.08). Comparing sealants, more segmentectomies were performed in patients with PGAS (P=0.0013) and their operative time was shorter (P=0.0002). PAL occurrences were not different. Length of stay (P=0.0045) and operative time (P=0.0002) were longer in patients with PEGS who had more postoperative complications (P=0.024). Conclusions: This study did not identify a positive effect of surgical sealants for preventing PAL. However it highlighted the need to rationalize their use.